DEVELOPMENT AND VALIDATION OF ANALYTICAL METHODOLOGY FOR DETERMINATION OF SYNTHETIC HORMONES 17α-ETHYNYLESTRADIOL AND LEVONORGESTREL IN SURFACE WATER - Monteiro, Bruna dos Reis (2015)
http://dx.doi.org/10.5902/2179460X17320The modern society has adopted a development system that has not taken into account the impacts on the environment. Recently, many substances discharged into bodies of water have been studied due to its capacity to cause changes in the endocrine system of living beings. One of these substances is the synthetic hormone 17a-ethynylestradiol, admittedly a powerful endocrine disruptor. This hormone is commonly used as one of the active ingredients of birth control pills, often associated with levonorgestrel. As these substances are disposed in bodies of water, a reliable analytical methodology is needed to quantify these species. Thus, this study aimed at the development and validation of an analytical methodology to determine the synthetic hormones 17α-ethynylestradiol and levonorgestrel in surface waters, using the high performance liquid chromatography technique. For the method validation the following parameters were evaluated: selectivity, precision, accuracy, linearity, limit of detection, limit of quantification and robustness. Satisfactory results were obtained in recovery studies with water samples fortified with the analytes. The developed and validated methodology was proved appropriate when tested with samples from the Sapucaí River in the city of Itajubá (MG).